The Influence of Auditor Independence on Audit Quality: A Qualitative Research - Kurniawan, Erwin (Manunggal Halim Jaya, 2023)
This qualitative research explores the influence of auditor independence on audit quality from diverse stakeholder perspectives within the auditing profession. The study aims to elucidate the perceptions, experiences, and challenges faced by auditors, corporate executives, and investors regarding auditor independence and its impact on audit quality. Semi-structured interviews and document analysis were employed to collect data, allowing for a comprehensive understanding of stakeholder perspectives. The findings reveal divergent viewpoints on the concept of auditor independence, with auditors emphasizing ethical principles and regulatory oversight, corporate executives highlighting the collaborative nature of the auditor-client relationship, and investors emphasizing the need for transparent financial reporting. Factors influencing auditor independence, such as auditor tenure, fee dependency, provision of non-audit services, and regulatory frameworks, were identified and discussed. Despite the complexities inherent in maintaining independence, stakeholders recognize the importance of regulatory interventions, ethical guidelines, and stakeholder engagement in safeguarding auditor independence and enhancing audit quality. Moving forward, efforts to enhance auditor independence and audit quality should prioritize regulatory reform, ethical leadership, and collaborative solutions within the auditing profession.